Application of polysaccharide-based edible coatings for shelf life extension and quality retention of fresh-cut pineapple - Azarakhsh, Nima (2013)
In the present study, polysaccharide-based edible coating formulations were investigated and optimised for fresh-cut pineapple (Ananas comosus L. cv. Josapine). The effects of alginate- and gellan-based coatings on respiration rate, physico-chemical properties, microbiological and sensory quality of fresh-cut pineapple during low temperature storage were determined. Finally, the effects of incorporation of natural antimicrobial agents in alginate-based coating on shelf life extension and quality retention of fresh-cut pineapple were evaluated. The coating treatment was carried out by dipping method. Five polysaccharide-based materials, namely chitosan, alginate, gellan, methyl cellulose and pectin, were screened as potential coatings for the fresh-cut fruit. Among these, alginate- and gellan-based coatings showed the most significant (p < 0.05) effect in reducing weight loss and respiration rate and also in maintaining firmness and sensory quality of fresh-cut pineapple. Response surface methodology was employed to optimise the most effective composition for the two coatings. Results obtained indicate that alginate-based formulation containing 1.29% (w/v) sodium alginate and 1.16% (w/v) glycerol, and gellan-based formulation containing 0.56% (w/v) gellan and 0.89% (w/v) glycerol, were the best. The results also showed that optimised alginate- and gellan-based formulations significantly (p < 0.05) reduced weight loss and respiration rate, and maintained the firmness and colour of fresh-cut pineapple during low temperature storage (10 ± 1 ºC; 65 ± 10% RH and 5 ± 1 ºC; 85 ± 10% RH) as compared to the control (uncoated sample). Results on the effects of natural antimicrobial agents (lemongrass, palmarosa, limonene and vanillin) incorporated into the optimised alginate-based formulation at different concentrations (0.1%, 0.3% and 0.5% w/v) on shelf life and quality of fresh-cut fruit showed that the former formulation incorporated with 0.3% (w/v) lemongrass significantly (p < 0.05) reduced yeast, mould and total plate counts while maintaining its sensory quality. Total plate counts and yeast and mould counts of uncoated samples reached 106 CFU/g after 8 days of storage at 10 ºC while using optimised alginate-based formulation incorporated with 0.3% (w/v) lemongrass extended the microbial shelf life of coated samples up to 12 days. Gas chromatographic-mass spectrometric analysis of volatile flavour compounds extracted from control and stored cut-fruits using solid-phase micro-extraction showed that the major volatile flavour compounds of Josapine pineapple were (i) methyl hexanoate; (ii) methyl 2-methyl butanoate; (iii) methyl 3-(methylthio)-propanoate; (iv) methyl octanoate and (v) methyl butanoate. Storage led to a significant (p < 0.05) reduction in the concentrations of major volatile flavour compounds in both coated and uncoated samples. However, this reduction in coated samples was significantly (p < 0.05) lower than uncoated samples. Images from scanning electron microscopy further demonstrated that the cell walls of coated fresh-cut pineapple had an almost similar intact appearance to those of fresh pineapple, while more cell wall disruption and higher microbial growth were observed in stored but uncoated samples. Thus, it can be concluded that optimised alginate-based edible coating formulation incorporated with 0.3% (w/v) lemongrass has the best potential to extend the shelf life up to 12 days and maintain the quality of fresh-cut pineapple.